Produtividade de grãos e acúmulo de nutrientes em solo adubado com dejetos animais durante nove safras - Cruz, Nayara Fernanda Ferraz da Silva (2019)
With the evolution of society in general, it is necessary to grow grain productivity. Thus, one of the environmental impacts caused is the overestimated use of agricultural fertilizers. Thus, taking advantage of the generation of regional waste such as the west of Paraná, with the bed of poultry and swine effluent, it is possible to incorporate alternatives to nutrient sources in agricultural soil. Thus, the hypothesis is that soybeans, corn, beans, wheat, oats and crambe may have positive effects on their productivity, due to the addition of avian litter (AC) and liquid pig slurry (DLS) in the soil. The objective was to verify the development of these crops and the cumulative effect of nutrients in the soil during nine consecutive harvests, from 2011 to 2016, analyzing the viability of organic fertilization and chemical changes in the soil. The treatments evaluated were three doses of litter bed, three of swine net waste and control with mineral fertilization. The experimental design was a randomized block design with three replicates. The experimental units were composed of 12 lines, 5 m long, spaced 34 cm, totaling 50 m2. After the harvest of each crop, the productivity (t / ha) was calculated and at the end of the nine harvests the accumulated grain yield. After the last harvest, soil samples were collected for phosphorus and potassium analysis. The data were submitted to analysis of variance and the means were compared by the Tukey test at 5% probability. The results showed that the DLS increased soil P content and the litter bed increased K. The grain yield did not differ according to the fertilization sources used in the crops of black oats, white oats, corn, beans and crambe. The DLS fertilization provided higher yields of wheat grains and also the accumulated grain yield of the nine harvests.